Analisis Pengaruh Pengendalian Internal dan Sistem Informasi Akuntansi Manajemen terhadap Kinerja Organisasi: Kajian Literatur - Reza Hamzani, Muhamad; Evi Nausta Pardede, Tiolina (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study aims to analyze the influence of internal control and management accounting information systems on organizational performance using a Systematic Literature Review approach. Internal control and management accounting information systems are essential components in management accounting practices that support effective resource utilization, accurate decision-making, and enhanced organizational accountability. This research employs a Systematic Literature Review method by reviewing various national and international journal articles published between 2015 and 2025. The research process includes keyword identification, article selection based on relevance and quality, content analysis, and synthesis of research findings. The results indicate that effective internal control can minimize the risk of deviations and improve compliance with organizational policies, while management accounting information systems provide relevant, accurate, and timely information to support planning, control, and performance evaluation. The integration of these mechanisms significantly contributes to the sustainable improvement of organizational performance